(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The developing number of publications related to coastal livelihood system in the last decade have significantly grown. To date, however, a study offering the comprehensive information related to the coastal livelihood system has not been conducted and also found in the electronic journal or proceeding. The purpose of this study is to present a bibliographic and bibliometric review of the numerous documents studying the coastal livelihood system. A systematic review involving bibliometric analysis was performed to carry out this study in which 198 eligible documents from Scopus database published in the period of 2013 – 2022 were used as research materials. Results revealed that the publication development of studies related to the inhabitants’ coastal livelihood system slightly soared from 2013 until 2022. Meanwhile, the citation development on the studies regarding the coastal livelihood system tended to moderately decrease between 2013 and 2022. Additionally, the productive and influential documents, authors, countries, affiliations, and sources contributed to the development of studies related to the coastal livelihood system. Moreover, some authors such as Islam, M. M., Rahman, M. A., and Hasan, M., and some countries such as United Kingdom, United States, Australia, India, and Bangladesh were the leading authors and countries generating the networking researches regarding the coastal livelihood system. Furthermore, most of the coastal people make beach tourism, fisher, and farmer as the livelihood system in the coastal zone. This study implies that the government must make the policy supporting the sustainable livelihood system of the coastal communities.